ANALISIS WACANA KRITIS PEMBERITAAN KEKERASAN BERBASIS GENDER DI SURAT KABAR HARIAN SUARA MERDEKA - Yuliyanto Budi Setiawan (Program Studi Ilmu Komunikasi FBIK Unissula, 2011)
Instead of giving empathy to the victims, newspapers tended to wrongly illustrate the violence as such that they were likely placing women in disgrace. The media described the women as the object of sexual fantasy, harassment, and violence. The problem was how the media presented the violence in their news. There seemed no empathy to the victims of violence against women. Such paradigm brought the victims into a symbolic violence. A critical discrouse analysis was necessary to fi nd out textual aspects, production, consumption, and socio-cultural contexts of gender-based violence news on a newspaper, like what this study had performed to Suara Merdeka daily. Using a qualitative descriptive technique with critical perspective, this study analyzed the qualitative data according to Norman Fairclough’s Critical Discourse Analysis. Having explored texts presented on the news on Suara Merdeka daily, the study found a gender bias. This study suggested that most journalists in Suara Merdeka hardly found opportunities to attend gender-related workshops, so that the news output they produced did not cover both side of story. Instead, the news presented were likely having a mindset that all the readers were males. Suara Merdeka had unfairly informed the news of the violence against women, placing them as the object who suffered by implicitly showing the superiority of men over them. Such mischief could have had been avoided had Suara Merdeka already performed in-depth training and knowledge improvement to the journalists in such that they became aware of women’s position in the gender-based violence.